Pengaruh Kepemimpinan Transformasional, Servant Leadership Dan Pembelajaran Organisasi Pada Kinerja Organisasi - Aprilia Lusiana Wollah; Bambang Nur Cahyaningrum; Ariyani Wahyu Wijayanti (Journal Of Business, Finance, and Economics (JBFE), 2020)
This study aims to determine how the influence transformational leadership, servant leadership and organizational learning on organizational performance in restaurants at Wonogiri Regency. The sample used was 154 employees of Restaurants in Wonogiri Regency, including Pak Glinding Restaurant, Titoti Wonogiri Restaurant, Karminah Restaurant, Pondok Dahar Tidar Raos Restaurant, Oke Resto, Pak To Buffet Restaurant, Titoti Ngadirojo Restaurant. Testing the hypothesis in this study using SEM (Structural Equation Modeling). Based on the results of the study, showed that the variables of transformational leadership and servant leadership, have a positive effect on organizational learning. The variable of organizational learning, has a positive effect on organizational performance. Keywords: Transformational leadership, servant leadership, organizational learning,  organizational performance